Genetic basis of unexplained erythrocytosis in Indian patients. (13th June 2019) - Mallik, Nabhajit; Sharma, Prashant; Kaur Hira, Jasbir; Chhabra, Sanjeev; Sreedharanunni, Sreejesh; Kumar, Narender; Naseem, Shano; Sachdeva, Man Updesh Singh; Ahluwalia, Jasmina; Malhotra, Pankaj; Varma, Neelam; Varma, Subhash; et al.
Abstract: Objective: To evaluate the spectrum of genetic defects in Indian patients with unexplained erythrocytosis. Methods: Fifteen families (18 patients) with unexplained erythrocytosis were enrolled after excluding polycythemia vera and secondary erythrocytosis. Focused Sanger sequencing from genomic DNA was performed for EPOR (exon 8), VHL (exons 2‐3), EGLN1 (exons 2‐5), EPAS1 (exon 12), and all exons of HBB, HBA1, and HBA2 genes. Results: Eleven of the 18 patients (including two pairs of brothers) had Chuvash polycythemia, that is, homozygosity for VHL :c.598C > T (p.Arg200Trp). Three patients (two of whom were brothers) had HBB mutations associated with increased oxygen‐affinity hemoglobin—one had a heterozygous Hb McKees Rocks HBB :c.438T > A (p.Tyr146*), and two brothers showed heterozygous Hb Rainier HBB :c.437A > G (p.Tyr146Cys). No pathogenic variants were found in the remaining four cases. Conclusion: A gene‐by‐gene Sanger sequencing approach could determine a genetic basis for erythrocytosis in 11 of the 15 (73%) Indian families, with homozygous VHL :c.598C > T (p.Arg200Trp) being the commonest pathogenic variant. This first study from the Indian subcontinent provides a rationale for analyzing this variant in patients with suspected congenital erythrocytosis from this region. Rare first occurrences of Hb McKees Rocks and Hb Rainier in Indians are also being reported.